Enhancement of human vision sensitivity features for watermarking performance using wavelet packet transformation [electronic resource] - Abduljabbar Hasan Mohammed Shaamala, 1984-; Azizah Abd. Manaf (2014)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2014